Self-activating liquid crystal devices for smart laser protection - Wang, Ling (Liquid crystals, 2016)
Lasers are now extensively used in a multitude of optical devices and photonic systems spanning from sensing, communication, entertainment, medical surgery to military applications. Direct accidental or intentional exposures to high power lasers may lead to severe temporary or even permanent harm of human eye, skin, or optical sensors. The effective laser protection and shielding are currently not only a subject of scientific research but also a potential public safety issue, therefore there is an urgent need to develop the intelligent laser protection devices for keeping human eyes, optical sensors, and other sensitive components from these unintended or intended damages by laser radiations without warning. Self-activating liquid crystal devices undoubtedly represent such an elegant example because they could be autonomously activated to block or attenuate the lasers when the laser intensity is higher than a maximum permissible exposure value. This review is devoted to summarising the up-to-date significant advances of self-activating liquid crystal devices for potential smart laser protection, including twist-aligned nematic liquid crystal devices, liquid crystal cored waveguide fibre arrays, and photovoltaic/pyroelectric-hybridised liquid crystal devices. Finally, the review concludes with the perspectives and challenges for the future development of self-activating liquid crystal devices. It is anticipated that this glimpse and further endeavours in the emerging field will help the researchers from different backgrounds towards the fabrication of highly efficient laser protection devices, their real-world widespread applications and beyond.